(untitled) (NIGERIAN JOURNAL OF PAEDIATRICS, 2024)
Summary: Plasma and blood volume of 30 children with severe protein-energy-malnutrition (PEM) and 10 well-nourished and age-matched children were determined by dye-dilution technique, using Evans blue. The mean values of plasma and blood volume of the patients were 60.03 + 16.20 and 94.84 + 25.25cc Kg - body weight, respectively. The corresponding values for the controls were 48.43 + 2.18 and 69.24 + 3.46cc Kg - body weight, respectively. These differences were significant (p<0.001 for plasma volume and p<0.003 for blood vol ume). Both plasma and blood volumes correlated with the degree of weight defiçit. The correlation co-efficient for plasma volume and the degree of weight deficit was I = 0.64, p<0.001. The corresponding value for blood volume was r=0.52, p<0.001. It is concluded from the present findings that there is a significant expansion of both plasma and blood volumes in severely malnourished children and these expansions correlated well with the degree of weight deficit.